2020
DOI: 10.1071/wf19132
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-intensity prescribed burns in two seasons on litterfall biomass and nutrient content

Abstract: Litterfall production and composition, fall pattern and nutrient content were studied in a mixed stand of Pinus nigra and Pinus pinaster (El Pozuelo), as well as in a pure stand of Pinus nigra (Beteta) in the Cuenca Mountains in order to determine the effect of two-season prescribed burning treatments. Needles were the most abundant fraction. Pinecone fraction decreased after burning in the mixed stand and the opposite occurred in the pure stand. The inflorescence fraction showed a decrease in the spring-burne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…When planning prescribed burns, forest managers must reach decisions in the face of uncertain conditions, as litterfall patterns depend on several variables that often interact in a complex way. The Bayesian approach seems to be a good statistical model for dealing with complex models (it enables the inclusion of multiple variables) and for implementing prior knowledge [29,36], thus enabling more robust conclusions to be obtained.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When planning prescribed burns, forest managers must reach decisions in the face of uncertain conditions, as litterfall patterns depend on several variables that often interact in a complex way. The Bayesian approach seems to be a good statistical model for dealing with complex models (it enables the inclusion of multiple variables) and for implementing prior knowledge [29,36], thus enabling more robust conclusions to be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Data provided by AEMET (1997-2018) [38] showed that a range of months with the most snowy days occurred mainly between December and March. During this period, for all treatments, branches represented on average 40% and 52% (MS and PS, respectively) of the total litterfall collected [36]. Branches may break as a result of the weight of accumulated snow, especially branches that are partly affected by fire.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations